PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN PRODUKSI KOPI DI DESA WEJANG MAWE KECAMATAN LAMBA LEDA TIMUR (The Role Of Agricultural Extension Workers In Increasing Coffee Production In Wejang Mawe Village, East Lamba Leda District) - Baeng, Benediktus Risaldo; Ngoni, Maria Salestina; Efridus, Heraklitus (Jurnal Ilmiah Sosio Agribis, 2025)
The purpose of this study was to find out how agricultural instructors contribute to the growth of coffee production in Wejang Mawe Village, East Lamba Leda District, East Manggarai Regency. In this study, a quantitative approach to descriptive research was employed as the research methodology. Multiple linear regression was employed in the data analysis for this study, while questionnaires and documentation were distributed as data collectio n technique.The resut of this study showed that the average impact of agricultural instructors' participation was 88.97%, based on descriptive statistical statistics, suggesting that their role is crucial in raising coffee output. indicating a normally distributed relationship between the function of agricultural instructors and coffee production, based on  the data normalcy test. The linearity test indicates that there is a linear relationship between variables (X) and (Y). According to the independent variables' multicollinearity test, the tolerance is less than 0.10 and the VIF score is greater than 10.00. The data on the contribution of agricultural instructors to the increase in coffee production demonstrated heteroscedasticity, as indicated by the partial heteroscedasticity of the variables (X₁). The findings of the t test for the Facilitator variable indicated that there was no significant impact of tcount and ttable, with 1.098 < 2.023 sig 0.298, on raising coffee production. There is no correlation between the innovator variable's tcount and ttable values (1.649 < 2.023 sig 0.108) and increased coffee production. Coffee production can be increased by the motivator variables that showed tcount and ttable values of 20.562 > 2.023 sig 0.000. Based on the F test's findings, there was no correlation between the Communicator variable's tcount and ttable values (-0.415 < 2.023 sig 0.681) and increased coffee production. While Ftable 0.05, Fcount = 469.275 > Ftable 4.113 sig 0.000. Since the error rate α=5% is significantly impacted by the independent variable. It followed that the variables X₁, X₂, X₃, and X₄ all simultaneously affect variable Y since H0 is rejected and Ha is approved.Keywords: Coffee, Role of Agricultural Instructor, Increasing, Production.